Modern Port-Industrial Town of Ploče, Croatia - Zrinka Barišić Marenić; Jasenka Kranjčević; Duje Jelčić (Prostor, 2025)
Ploče is the only town in Croatia that was planned and built on the Adriatic coast as a result of social planning after World War II. As a planned port-industrial town, Ploče has been neglected in architectural research by experts and the wider public. Therefore, the subject of this research is the unexplored modern public architecture (built 1952-1970) that contributed to the transformation from a port-industrial town to a town with increasingly urban characteristics. The work is based on the research of scarce primary archival material, field research and comparison of public buildings of the same purpose built in Croatia in the same or similar time period. As Ploče has become increasingly urban over time, green areas have been analysed and arranged as one of the indicators of urbanity. Research and valorisation of the contemporary public architecture of Ploče has shown that it represents a piece of valuable Croatian architectural heritage, which has been neglected until now.